Recurrent oligodendroglioma with changed 1p/19q status. Issue 2 (10th February 2022) - Barresi, Valeria; Mafficini, Andrea; Calicchia, Martina; Piredda, Maria Liliana; Musumeci, Angelo; Ghimenton, Claudio; Scarpa, Aldo
Abstract : We report a case of oligodendroglioma that had consistent histopathological features as well as a distinct change in 1p/19q status in the second recurrence, after temozolomide chemotherapy and radiotherapy. The first tumor recurrence had oligodendroglial morphology, IDH1 R132H and TERT promoter mutations, and 1p/19q codeletion detected by fluorescent in situ hybridization (FISH). Copy number analysis, assessed by next‐generation sequencing, confirmed 1p/19q codeletion, and disclosed loss of heterozygosity (LOH) of chromosomes 4 and 9 and chromosome 11 gain. The second recurrence featured not only oligodendroglial morphology but also the appearance of admixed multinucleated giant cells or neoplastic cells having oval nuclei and mitoses and showing microvascular proliferation; it maintained IDH1 R132H and TERT promoter mutations, acquired TP53 mutation, and showed 19q LOH, but disomic 1p, detected by FISH. Copy number analysis depicted LOH of chromosomes 3p, 13, and 19q, 1p partial deletion (1p chr1p34.2‐p11), and gain of chromosomes 2p25.3‐p24.1, 8q12.2‐q24.3, and 11q13.3‐q25. B‐allele frequency analysis of polymorphic sites disclosed copy‐neutral LOH at 1p36.33‐p34.2, supporting the initial deletion of 1p, followed by reduplication of 1p36.33‐p34.2 alone. These findings suggest that the two tumor recurrences might have originated from an initial neoplastic clone, featuring 1p/19q codeletion and IDH1 and TERT promoter mutations, and have independently acquired other copy number alterations. The reduplication of chromosome 1p might be the result of temozolomide treatment, and gave rise to false negative 1p deletion detected by FISH. The possibility of 1p copy‐neutral LOH should be considered in recurrent oligodendrogliomas with altered 1p/19q status detected by FISH.